Computational aspects of host-parasite phylogenies - Stevens, J. (Briefings in bioinformatics, 2004)
Computational aspects of host-parasite phylogenies form part of a set of general associations between areas and organisms, hosts and parasites, and species and genes. The problem is not new and the commonalities of exploring vicariance biogeography (organisms tracking areas) and host-parasite co-speciation (parasites tracking hosts) have been recognised for some time. Methods for comparing host-parasite phylogenies are now well established and fall within two basic categories defined in terms of the way the data are interpreted in relation to the comparison of host-parasite phylogenies, so-called a posteriori, eg Brooks' Parsimony Analysis (BPA), or a priori, eg reconciled trees and other model-based methods, as implemented in the program TreeMap; the relative merits of the two philosophies inherent in these two approaches remain hotly debated. This paper reviews the computational methods currently available to analyse host-parasite relationships.